Mediastinal contrast extravasation after injection via central venous catheter with follow-up venography: a case report - Marko Kastelic; Igor Kocijančič; Dašmir Nuredini; Jernej Vidmar (Zdravniški Vestnik, 2021)
A central venous catheter can occasionally be used for contrast injection during a CT scan, with mediastinal contrast extravasation as a possible rare complication in this setting. According to the published cases, interventional venography has never been performed to assess the venous system directly. We present a case of mediastinal contrast extravasation with follow-up venography, which clearly depicted a subintimal leak and no evidence of sustained extravasation. The contrast was reabsorbed shortly after the extravasation with no adverse effects for the patient. The presented case illustrates the importance of recognition of proper positioning of central venous catheters before performing angiographies with relatively high flow velocity, such as CT angiography, as well as the importance of performing staff being familiar with different aspects of working with central venous catheters.